Is organic livestock farming more welfare-friendly than its conventional counterpart? – A systematic literature review in terms of animal health, welfare and management - K. Wagner; S. March; D. Haager; J. Brinkmann (Organic Agriculture, 2026)
Abstract Organic farming is widely regarded as an animal-friendly husbandry system that benefits animal welfare. However, very little information is available on the situation in practice that can answer the question as to whether organic livestock farming is more welfare-friendly than its conventional counterpart. Therefore, the authors of this paper carried out a comprehensive systematic literature analysis using various databases. Eighty-six peer-reviewed studies published between January 1990 and June 2023 were considered, which included 623 comparative pairs. Across all common livestock species and type of production within Europe and North America, the results provided no clear picture of whether organic farming has a positive effect on the individual welfare outcome than conventional farming. The comparative studies evaluated mostly focused on individual aspects of animal welfare (e.g. animal health) and predominantly on dairy cows. No fundamental differences were found in animal health except for claw and leg health (in cattle and pigs). This indicates that management factors are of greater importance than the farming system itself. Organic farming showed advantages in 28% of the comparative pairs compared to conventional farming, in 56% no clear differences could be found. The literature review showed that whilst organic farming has the potential to achieve good standards of animal welfare (e.g. regarding lameness), it may not be beneficial if accompanied by sub-optimal management (e.g. regarding pasture parasites). In order to safeguard animal welfare within the context of organic certification, a transparent, standardised and feasible animal welfare audit concept using animal-based indicators, should be implemented.